Pengaruh Kualitas Pelayanan dan Profesionalisme Guru terhadap Kepuasan Siswa SMAN 1 Bulakamba - Siti Marselia; Azizah Indriyani; Slamet Bambang Riono; Muhammad Syaifulloh; Gian Fitrialisma (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of service quality and teacher professionalism on student satisfaction at SMAN 1 Bulakamba. The background of this research is based on the importance of the role of schools in providing optimal education services and the professionalism of teachers as a key factor in creating an effective and enjoyable learning process. This research uses a quantitative approach with an associative method. The population in this study consists of all students of SMAN 1 Bulakamba, totaling 1,258 students. The sample was taken using the Slovin formula with a 5% error level, resulting in a sample of 304 respondents. Data collection techniques were carried out through observation, documentation, and questionnaires using a Likert scale. Data analysis was conducted using SPSS software, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination tests. The results of the study show that both service quality and teacher professionalism significantly affect student satisfaction, both partially and simultaneously. These findings suggest that improving service quality and teacher professionalism can directly enhance student satisfaction in the learning process at school.